Strategi Pemasaran Produk Bank Syariah Berbasis Nilai Syariah di Desa Mojoarno - Syahru Ramadlan Al-Ghoffar; Peni Haryanti (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to analyze the marketing strategies of Islamic bank products based on sharia values implemented in Mojoarno Village (Ikhsanudin et al. 2024). The background of this research is the increasing development of Islamic banking in Indonesia which is not always followed by sucient understanding of sharia nancial products at the rural level (Qothrunnada et al. 2023). This condition requires Islamic banks to design marketing strategies that are not only focused on product promotion, but also on education, empowerment, and strengthening public trust (Damayanti 2023). This research uses a qualitative case study approach on an Islamic bank that actively conducts marketing activities around Mojoarno Village (Yin 2018). Data were collected through in-depth interviews with bank marketing sta , religious leaders, and customers, participatory observation in socialization and religious activities, as well as documentation of promotional materials and internal reports (Miles and Huberman 2014). The data were analyzed through data reduction, data display, and conclusion drawing with source and technique triangulation to ensure validity. The ndings show that marketing strategies integrated with sharia values—such as justice, transparency, and avoidance of riba, gharar, and maysir—combined with religious and cultural approaches through mosques and majelis taklim can increase public literacy and interest in Islamic bank products (Rahman, Aji, and Sopingi 2023). However, several challenges still remain, including low initial nancial literacy, strong informal nancial practices, and limited marketing resources in rural areas (Syifa, Nasution, and Inayah 2024). The implications of this research emphasize the importance of synergy between Islamic banks, religious leaders, and local communities to develop sustainable sharia-based marketing models in rural contexts.